Paris for two - Stone, Phoebe, 1947- (Arthur A. Levine Books, an imprint of Scholastic Inc., 2016)
Twelve-year-old Petunia is used to living in the shadow of her fourteen-year-old half-sister, Ava, their mother's favorite, but now that the whole family has moved to Paris for a year, Pet finds herself stepping into the light, making new friends, uncovering secrets, and, inspired by the classic French dolls she has found, revealing an unexpected talent for designing dresses--and her beautiful sister does not take it well.